Sustainable Conversion of Mixed Organic Waste into High-Quality Bio-Briquettes through Controlled Carbonization and Densification for Community-Based Energy Systems - Rahmat Sabani; Ari Handono Ramelan; Surya Abdul Muthalib; Yuhendra AP (International Journal of Natural Science Studies and Development (IJOSS), 2025)
The conversion of organic waste into renewable solid fuel represents a promising strategy to simultaneously address waste management challenges and local energy demand. This research evaluates the technical performance, energy characteristics, and environmental implications of producing bio-briquettes from mixed organic waste through controlled carbonization and densification. Mixed organic biomass representative of community waste streams was carbonized using an insulated drum retort under controlled temperature conditions, followed by grinding and densification with a starch-based binder and a low-dose potassium nitrate additive. The resulting bio-briquettes were characterized in terms of physical, mechanical, thermal, and combustion properties. In addition, mass and energy balance analyses and a cradle-to-gate life cycle assessment were conducted to evaluate process efficiency and environmental performance. The results demonstrate that carbonization temperature strongly influences char yield and fuel quality, with optimal performance observed at approximately 400 °C. Under these conditions, the bio-briquettes achieved a high calorific value of approximately 24.3 MJ kg⁻¹ (≈ 5,800 kcal kg⁻¹), high density, adequate compressive strength, and stable combustion behavior. The addition of potassium nitrate significantly improved ignition performance when applied at appropriate concentrations. Life cycle assessment results indicate that bio-briquette production from mixed organic waste results in substantially lower greenhouse gas emissions compared with fossil fuels delivering equivalent energy. Overall, this research confirms that bio-briquettes derived from mixed organic waste represent a technically feasible and environmentally sustainable waste-to-energy solution suitable for decentralized, community-based energy systems.